Building an innovative learning organization : a framework to build a smarter workforce, adapt to change, and drive growth - Sarder, Russell, 1973- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2016)
Institute a culture of learning to boost organizational performance and agility What makes organizations successful' Today, most successful companies are learning organizations. Building an Innovative Learning Organization shows you how to join their ranks and bring your organization up to the head of the class. This book is a practical, actionable guide on how to boost performance, successfully manage change, and innovate more quickly. Learning organizations are composed of engaged, motivated employees who continually seek improvement, which leads to organizational agility and the ability to innovate ahead of the curve. When you encourage learning at every level, from the intern to the C suite, you gain a more highly skilled workforce with a greater ability to act in any situation. Building an Innovative Learning Organization shows you how to create this culture in your organization, with detailed explanations, practical examples, and step-by-step instructions so you can get started right away. Written by a recognized thought leader in the training industry, this informative and insightful guide is your roadmap to a more effective organization. You will discover how to: -Attract, retain, and motivate the best employees -Become a more innovative and agile organization -Create a culture of continuous self-improvement -Encourage learning at all levels and translate it into action Learning and education doesn't end at graduation-it's a lifelong process that keeps you relevant, informed, and better able to achieve your goals. These same benefits apply at the organizational level, making the culture self-sustaining: learning organizations attract top workers, who drive the organization forward, which attracts more top workers. If you want the best people, you have to be their best option. Building an Innovative Learning Organization gives you a blueprint for building a culture of learning, for a stronger, more robust organization.
Authors and Educators -- Learning Managers and Learning Professionals -- Partial List of Chief Executive Officers, Chief Learning Officers, Chief Information Officers, Authors, and Thought Leaders Interviewed by Sarder TV -- References and Resources -- References -- Useful Websites -- Acknowledgments -- About the Author -- Index -- End User License Agreement.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Organizational learning; Organizational change; Apprentissage organisationnel; Changement organisationnel; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Organizational change; Organizational learning